Cambodia : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The rapid spread of the virus in Cambodia during 2021 has set the economy back again, after external demand collapsed in 2020. The authorities responded to the crisis with measures to support households and firms, including increased healthcare spending; a new system of cash transfers to vulnerable households; loans and guarantees; tax breaks; and wage subsidies and retraining. Despite these measures, growth is estimated to have contracted by -3.1 percent in 2020. Growth in 2021 is expected to be 2.2 percent, slowly recovering to pre-crisis rates of around 6 1/2 percent.